156 - PERFORMANCE OF MOTOR SKILLS IN CHILDREN DESCENDANTS OF SLAVES AFRICAN TWO COMMUNITIES, ONE RURAL AND ONE URBAN CITY OF MACAPÁ – AP (Fiep Bulletin - online, 2011)
The aim of this study was to verify and analyze the performance of motor skills in children descendants of two communities, one rural and one urban in the city of Macapá, Ap. The instrument used to collect data was TGMD-2 test (Test of Gross Motor Development, 2nd edition), proposed by Ulrich (2000), whose objective is to identify an index of gross motor skill of locomotor and object control. After analyzing the data obtained, it was observed that children of the urban community were classified as poor in the skills of locomotion and the children of the rural community as Below Average. The control skills of objects children two communities were classified Below Average. When classified by Gross Motor Quotient thick community children reached the Urban Poor and classification of rural community classified as below average. It concluded that the two groups of children have difficulties to be overcome in the development of motor skills.
Keywords: Motor Skills; Children; Urban Zone and Rural Zone